A review of MPTP-induced parkinsonism in adult zebrafish to explore pharmacological interventions for human Parkinson’s disease - Bagwell, Emmeline; Larsen, Jessica (Frontiers in Neuroscience, 2024)
Novel work in adult zebrafish, Danio rerio, to recapitulate human neurodegenerative disease has proven useful in both pharmaceutical development and research on genetic disease.Due to high genetic homology to humans, affordable husbandry, relatively quick life cycle breeding times, and robust embryo production, zebrafish offer a promising model to test pharmaceutical performance in a high throughput, in vivo setting. Currently, most research in zebrafish models of Parkinson's Disease induces the disease during larval or embryonic stage organisms due to ease of administration, with advancement through developmental stages taking only a matter of days 1 . The use of early-stage organisms limits the usability of zebrafish as models for adult disease and specifically age-related neurodegenerative conditions. Recently, researchers have sought to extend the usability of zebrafish into models for Parkinson's Disease. Specifically, 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) has emerged as a prodrug that upon injection well-encompasses the biochemical mechanisms and symptomology associated with Parkinson's Disease. By utilizing MPTP in an adult zebrafish model, advancements in Parkinson's Disease research may be achieved. This paper highlights the recent research on this model, comparing it to the human form of Parkinson's Disease.